Commentary: Outbreak of Chikungunya in Pakistan - Mallhi, Tauqeer Hussain; Khan, Yusra Habib; Khan, Amer Hayat; Tanveer, Nida; Khan, Omaid Hayat; Aftab, Raja Ahsan (Frontiers Media, 2017)
Rauf et al. in their recent correspondence in “Lancet Infectious Diseases” reported the first chikungunya outbreak in Karachi, Pakistan with 30,000 suspected and 4,000 confirmed cases (1). However, these estimates have been denied in a subsequent report by the National Institute of Health (NIH) indicating 818 suspected and 82 laboratory-confirmed cases of chikungunya (2). Rauf and colleagues have highlighted warm climate and wretched sanitary conditions as contributing factors of current outbreak and urge national and international health-organizations to address these momentous issues (1). We agree that climatic features and sanitation issues potentially lead to vector proliferation and the importance of these concerns cannot be disregarded. However, we felt inclined to share our point of view about the recent outbreak of chikungunya in Pakistan. We believe that there are some more important factors that should be considered as causes of this outbreak and must be addressed by the Government of Pakistan in haste to quell the further disease spillover. One of these factors is unchecked cross-border movements between Pakistan and India.